High-throughput drug screening identifies fluoxetine as a potential therapeutic agent for neuroendocrine prostate cancer - Chen, Lei; Ji, Yiyi; Li, Ang; Liu, Bo; Shen, Kai; Su, Ruopeng; Ma, Zehua; Zhang, Weiwei; Wang, Qi; Zhu, Yinjie; Xue, Wei (Frontiers in Oncology, 2023)
Neuroendocrine prostate cancer (NEPC) is an aggressive subtype of prostate cancer with poor prognosis and resistance to hormone therapy, which has limited therapeutic approaches. Here, we performed a high-throughput drug screening and identified fluoxetine, originally an FDA-approved antidepressant, as candidate therapeutic agent for NEPC. In vitro experiments revealed that fluoxetine effectively curbed the neuroendocrine differentiation and inhibited the cell viability by targeting the AKT pathway. Preclinical test in NEPC mice model (PBCre4: Ptenf/f;Trp53f/f;Rb1f/f) showed that fluoxetine effectively prolonged the overall survival, and reduced the risk of tumor distant metastases. Altogether, this work repurposed fluoxetine for antitumor application, and supported its clinical development for NEPC therapy, which may provide a promising therapeutic strategy.